Exotic Pollen in Sediments from the High Arctic Lake Tenndammen, Svalbard Archipelago: Diversity, Sources, and Transport Pathways - Poliakova, Anastasia; Brown, Antony G.; Alsos, Inger G. (Palynology, 2024)
We analysed the pollen and spores extracted from 73 samples of lacustrine sediments from Colesdalen in Svalbard (Lake Tenndammen) as well as 10 soil samples collected from the lake's shores. In total, 56 pollen taxa were recorded from the sediments spanning the last 800 years, whilst 35 pollen types were found in the soil samples. Pollen was categorised as (i) regional (from Svalbard); (ii) exotic to Svalbard today; or (iii) of mixed or unclear origin. Major changes in pollen assemblages after ca 1900 CE were associated with human impact. Around 1920 CE, the first signs of introduced plant taxa were identified, by the presence of Apiaceae and Fabaceae pollen. Additionally, large-sized pollen with a thick exine and annulus diameter of 10.6–13 µm, identified as Poaceae/Cerealia type, was constantly present after ca 1920 CE. Other exotic pollen, including Ulmus, Juglans, and tropical pollen of Albizia/Mimosa type, Eucalyptus type, Acalypha type, and Passiflora type, are found only during the 1930s to 1960s, which is the period associated with the most intensive mining activity and human migration to and from Colesdalen. Furthermore, the repeated occurrence of Myrica (gale) type and Erica type occurring both in the lake sediment and in the soil samples is best explained by the migration of geese from Scotland (UK). Our research demonstrates how precisely human history can be reflected in the lake sediments of the Arctic environment.